Loss of the TGFβ-activating integrin αvβ8 on dendritic cells protects mice from chronic intestinal parasitic infection via control of type 2 immunity. - John J Worthington; Joanna E Klementowicz; Sayema Rahman; Beata I Czajkowska; Catherine Smedley; Herman Waldmann; Tim Sparwasser; Richard K Grencis; Mark A Travis (PLoS Pathogens)
Chronic intestinal parasite infection is a major global health problem, but mechanisms that promote chronicity are poorly understood. Here we describe a novel cellular and molecular pathway involved in the development of chronic intestinal parasite infection. We show that, early during development of chronic infection with the murine intestinal parasite Trichuris muris, TGFβ signalling in CD4+ T-cells is induced and that antibody-mediated inhibition of TGFβ function results in protection from infection. Mechanistically, we find that enhanced TGFβ signalling in CD4+ T-cells during infection involves expression of the TGFβ-activating integrin αvβ8 by dendritic cells (DCs), which we have previously shown is highly expressed by a subset of DCs in the intestine. Importantly, mice lacking integrin αvβ8 on DCs were completely resistant to chronic infection with T. muris, indicating an important functional role for integrin αvβ8-mediated TGFβ activation in promoting chronic infection. Protection from infection was dependent on CD4+ T-cells, but appeared independent of Foxp3+ Tregs. Instead, mice lacking integrin αvβ8 expression on DCs displayed an early increase in production of the protective type 2 cytokine IL-13 by CD4+ T-cells, and inhibition of this increase by crossing mice to IL-4 knockout mice restored parasite infection. Our results therefore provide novel insights into how type 2 immunity is controlled in the intestine, and may help contribute to development of new therapies aimed at promoting expulsion of gut helminths.